Taxpayer Awareness Among Gold Jewelry Dealers Following Ministry of Finance Regulation No. 48/2023 (E-Jurnal Akuntansi, 2026)
This study aimed to determine the awareness among gold jewelry dealers who are taxpayers, regarding the Ministry of Finance Regulation No. 48 of 2023. This research is novel in its comprehensive coverage of the new tax regulation spanning from upstream to downstream processes in the gold jewelry industry. It has the potential to increase tax revenue from this sector; however, understanding the awareness of these taxpayers is crucial as it influences their compliance. A significant number of gold jewelry dealers were not aware of the new regulation, and some had not even implemented the previous regulations. Data were collected through questionnaires and interviews. A qualitative descriptive analysis was employed to analyze the awareness of gold jewelry dealers who are taxpayers. The findings of this study indicate that the awareness of these taxpayers regarding the new regulation remains low. Consequently, further socialization is necessary to yield a positive and significant impact on taxpayer compliance.
Keywords: Gold jewelry dealers; Income Tax, Value Added Tax; Ministry of Finance Regulation No 48 Year 2023